A Mixed Method Evaluation of Practitioners' Perspectives on Implementation Strategies for Healthy Eating and Active Living Policy, Systems, and Environmental Changes. - Houghtaling, Bailey; Pradhananga, Nila; Holston, Denise; Cater, Melissa; Balis, Laura (Journal of Public Health Management & Practice)
Context: The National Cooperative Extension System is a leader in delivering healthy eating and active living (HEAL) policy, systems, and environmental (PSE) changes; however, these interventions are challenging, and technical assistance efforts often misalign with implementation science concepts. Objective: The study objective was to understand the importance of implementation strategies and tailoring needs to support Louisiana Nutrition and Community Health (NCH) practitioners' delivery of rural HEAL PSE changes. Design: An explanatory sequential mixed method study design was used, including a survey to rank the importance of implementation strategies for HEAL PSE changes and a follow-up interview. A review of available implementation strategies (practice activities/resources) for Louisiana HEAL PSE changes was also conducted. Setting: This study occurred within Louisiana and focused on NCH practitioners' ongoing HEAL PSE change efforts throughout the state, with emphasis on rural community settings. Participants: All NCH practitioners were eligible to participate. "Practitioners" included Extension NCH administrators and agents/educators directly delivering HEAL PSE changes. Main Outcomes: The main quantitative outcome was the ranked importance of implementation strategies to support NCH practitioners' delivery of HEAL PSE changes. For explanatory interviews, perceptions of higher and lower ranked implementation strategies and tailoring opportunities were of interest. The alignment of available activities/resources with possible implementation strategies was also assessed. Results: Highly ranked implementation strategies focused on engaging dedicated community partners and community members and starting small to ensure success, generate buy-in, and demonstrate feasibility. Opportunities for capacity building in these areas were identified. A lower ranked implementation strategy, changing organizational structures, was considered less likely to occur but possibly necessary to improve job satisfaction, retention, and return on investment. Available activities/resources overlapped with a few available implementation strategies. Conclusions: This study identified opportunities to use implementation science concepts to improve program support for NCH practitioners delivering complex HEAL PSE changes.